2012
DOI: 10.1371/journal.pone.0046689
|View full text |Cite
|
Sign up to set email alerts
|

Chip-Based Comparison of the Osteogenesis of Human Bone Marrow- and Adipose Tissue-Derived Mesenchymal Stem Cells under Mechanical Stimulation

Abstract: Adipose tissue-derived stem cells (ASCs) are considered as an attractive stem cell source for tissue engineering and regenerative medicine. We compared human bone marrow-derived mesenchymal stem cells (hMSCs) and hASCs under dynamic hydraulic compression to evaluate and compare osteogenic abilities. A novel micro cell chip integrated with microvalves and microscale cell culture chambers separated from an air-pressure chamber was developed using microfabrication technology. The microscale chip enables the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 56 publications
(78 reference statements)
4
85
0
1
Order By: Relevance
“…Adipose has emerged as a reliable source because tissue can be easily obtained in larger quantities through lipoaspiration compared with bone marrow aspiration [30]. Based on this, several groups have compared the osteogenic potential of MSCs derived from the adipose tissue with that of MSCs obtained from bone marrow [31,[52][53][54][55][56]. Although results suggesting one source as favorable to another have been mixed [30][31][32], bone marrow overall was found to be superior as far as ALP activity, mineral deposition, and the expression of Values are mean ± standard deviation (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose has emerged as a reliable source because tissue can be easily obtained in larger quantities through lipoaspiration compared with bone marrow aspiration [30]. Based on this, several groups have compared the osteogenic potential of MSCs derived from the adipose tissue with that of MSCs obtained from bone marrow [31,[52][53][54][55][56]. Although results suggesting one source as favorable to another have been mixed [30][31][32], bone marrow overall was found to be superior as far as ALP activity, mineral deposition, and the expression of Values are mean ± standard deviation (n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…Using hydraulic pressure to add cell stress, they saw increases in bone matrix formation in both cell types; however, stimulated BMSCs showed greater staining in Alizarin Red S and ALP assays which is indicative of osteogenesis. They concluded that BMSCs were more susceptible to changes in osteogenic differentiation under mechanical stimulation than ADSCs (42). This conclusion seems reasonable when one considers the weight bearing responsibility and mechanical stability demand of the human skeletal system, which is likely a manifestation of the susceptibility and responsiveness of osteoblastic precursor and BMSC populations to such mechanical forces.…”
Section: Tissue-specific Stem Cells Benefiting Lineage-specific Diffementioning
confidence: 99%
“…3, 6, 21, 31, 44 For example, Butcher et al (2006) applied mechanical squeezing force on a chamber filled with liquid and cylindrical collagen disks to obtain a uniform compressive strain. 6 Gould et al (2012) used elliptical compression springs to clamp anisotropic 3D collagen hydrogels in a biaxial strain bioreactor to control the ellipsoidal deformation ratio using step motors.…”
Section: Introductionmentioning
confidence: 99%